Qualitative research in education: focus and methods - SHERMAN, Robert R. Robert R. Sherman; SHERMAN, Robert R. Robert R. Sherman; WEBB, Rodman B. Rodman B. Webb (London: Routledge, 1988)
Published in the year 1988, Qualitative Research In Education is a valuable contribution to the field of Education.
Includes index.
Keywords: Education research